PENGARUH PERBEDAAN SUHU DAN WAKTU PENGERINGAN TERHADAP KARAKTERISTIK IKAN ASIN SEPAT SIAM (Trichogaster pectoralis) DENGAN MENGGUNAKAN OVEN - Angga Riansyah; Agus Supriadi; Rodiana Nopianti (Universitas Sriwijaya, 2013)
The researce objective was to the effect of different drying temperatures and times on the characteristics of fish salted Siamese gourami (Trichogaster pectoralis) using oven. This research was conducted on October until November 2012 in the Fishery Processing Technology Laboratory, Faculty of Agriculture and Bioproses Laboratory, Faculty of Engineering, Sriwijaya University of Indralaya. The research used Factorial Randomized Completely Block design with 3 difference drying temperature and 5 difference time then 2 replicated. The treatment of temperature (50oC, 60oC and 70oC) and time (0, 6, 12, 18 and 24 hours). Parameters observed were moisture content, ash content, fat content, protein content, carbohydrate content, hedonic quality test : appearance, aroma, flavor and texture. The results showed that the difference drying temperature and drying time was significant on moisture content, ash content, fat content, protein content, carbohydrate content, hedonic quality test : appearance, aroma, flavor and texture. Interaction of kinds of different drying temperatures and times had significant effect on moisture content, ash content, protein content and carbohydrate content. The best treatment was combination of T3t2 with oven temperature 70Â°C for 12 hours with moisture content 39.05%, ash content 6.85%, protein content 42.41 %, fat content 10.22%, carbohydrate content 1.66%, appearance 7.8, aroma 7.08, and flavor 7.08 and texture 7.82